2022
DOI: 10.1111/asj.13786
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships among emu populations in Japanese farms based on mitochondrial and microsatellite DNA polymorphisms

Abstract: Emus (Dromaius novaehollandiae) are expected to become a novel poultry species for producing eggs, meat, and oil. In our previous studies, Japanese emu populations were predicted to have reduced genetic diversity through inbreeding. For a sustainable emu industry in Japan, it is necessary to understand the current genetic structure and relationships in dispersed farms. In this study, we investigated the genetic structure and relationships of six Japanese emu farms based on mitochondrial DNA and microsatellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 24 publications
4
8
0
Order By: Relevance
“…The inbreeding coefficients ( F IS ) of the TSP, OEF2016, OEF2017, FGP, and KGP were 0.320, 0.198, 0.175, 0.237, and 0.305, respectively. These results suggest that all tested Japanese farmed populations tend to inbreed and that TSP is in the most profound condition, consistent with our previous reports 5 , 27 . Pedigree analysis using Colony2 software showed that there were three full-sib pairs and 69 half-sibs in the analyzed 253 individuals (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The inbreeding coefficients ( F IS ) of the TSP, OEF2016, OEF2017, FGP, and KGP were 0.320, 0.198, 0.175, 0.237, and 0.305, respectively. These results suggest that all tested Japanese farmed populations tend to inbreed and that TSP is in the most profound condition, consistent with our previous reports 5 , 27 . Pedigree analysis using Colony2 software showed that there were three full-sib pairs and 69 half-sibs in the analyzed 253 individuals (Fig.…”
Section: Resultssupporting
confidence: 92%
“…In a previous study, we suggested that TSP and FGP/KGP are genetically different from OEF based on analyses using SSR markers and mtDNA haplotypes 5 . Therefore, we used samples derived from the same populations as in our previous studies and included a large number of individuals with OEF as controls.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations